2019
DOI: 10.3390/polym11121961
|View full text |Cite
|
Sign up to set email alerts
|

Bioresorbable Stent in Anterior Cruciate Ligament Reconstruction

Abstract: The exact causes of failure of anterior cruciate ligament (ACL) reconstruction are still unknown. A key to successful ACL reconstruction is the prevention of bone tunnel enlargement (BTE). In this study, a new strategy to improve the outcome of ACL reconstruction was analyzed using a bioresorbable polylactide (PLA) stent as a catalyst for the healing process. The study included 24 sheep with 12 months of age. The animals were randomized to the PLA group (n = 16) and control group (n = 8), subjected to the ACL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 54 publications
0
10
1
Order By: Relevance
“…8 In this study, the bone tunnels were divided into thirds as described previously. 10,48 In our study, there were no significant differences between femoral and tibial tunnels in the control group for trabecular bone analysis or BMD. Nevertheless, some differences were seen when using orthobiologics.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…8 In this study, the bone tunnels were divided into thirds as described previously. 10,48 In our study, there were no significant differences between femoral and tibial tunnels in the control group for trabecular bone analysis or BMD. Nevertheless, some differences were seen when using orthobiologics.…”
Section: Discussioncontrasting
confidence: 47%
“…3 In a rabbit model using suspensory fixation, graft-tunnel motion was greatest at the tunnel apertures with closer apposition of bone to tendon seen at the tunnel exits than at the tunnel aperture. 31 Ficek et al 10 reported the bone tunnel enlargement in sheep using suspensory fixation and Achilles tendon autograft. After 12 weeks, the tunnel tended to be wider at its aperture in the control group, whereas this was not seen in the group using a poly-96L/4D-lactic acid stent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The silk–collagen scaffold was discovered to have good biocompatibility and biomechanical properties [ 12 ]. However, in the early postoperative period, limited ingrowth of the newly regenerated connective tissue in the knee cavity restricted ligament regeneration, and bone tissue in the bone tunnel disrupted graft–bone healing [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%